Peranan Bangunan Berpentas Prosenium dalam Tradisi Persembahan Bangsawan di Sarawak: The Function of A Proscenium Staged Building in the Bangsawan Performance Tradition in - Nur Afifah Vanitha Abdullah (Wacana Seni Journal of Arts Discourse, 2017)
Since the early emergence of the Malay opera in Peninsular Malaya, Singapore and Sarawak, its performance has always taken place on a proscenium stage. Bangsawan troupes with big funds usually rented cinema buildings, where else troupes with small funds erected their own proscenium stage to perform. Thus the tradition of performing bangsawan on this type of stage is noted as among the obstacles for the continuity of bangsawan in Sarawak since the 1990s. Theatre activists, especially the amateurs tend to avoid staging the bangsawan because of its rigid requirement for the proscenium stage. A bigger budget is required to rent a premise with a proscenium stage for bangsawan as compared to other theatre genres. Hence, the concept of "nest" in Richard Schechener's (1988) "performance theory" is applied to answer, "what is the function of the proscenium staged building's architechture to the bangsawan performance tradition in Sarawak?" A fundamental research with qualitative method was designed. Content analysis was choosen as the main research instrument to gather data from books, journal articles, and recordings of previous bangsawan performances. Observation was also carried out on the recent preview of "Bangsawan Sultan Tengah" performance organised by Dewan Bahasa dan Pustaka, Sarawak branch, on December 2015. The findings in this article show that the architecture of the proscenium staged building is very much related to the performance process and staging structure of the bangsawan. The front of house and back stage are relevant to a few activities related to the gathering process in this theatre. Besides that, although the performance accessories such as its "Kota Bum", side wings, and jala have no direct influence on the staging of bangsawan, these items have their specific place and function as part of the performance equipment for this theatre.